2007
DOI: 10.1002/jcc.20616
|View full text |Cite
|
Sign up to set email alerts
|

Origin of intrinsic 310‐helix versus strand stability in homopolypeptides and its implications for the accuracy of the Amber force field

Abstract: Current all-atom force fields often fail to recognize the native structure of a protein as the lowest free energy minimum. One possible cause could be the mathematical form of the potential based on the assumption that the conformation of a residue is independent of its neighbors. Here, using quantum mechanical (QM) methods (MP2/6-31g**//HF/6-31g** and MP2/cc-pVDZ//cc-pVDZ//HF/cc-pVDZ), the intrinsic correctness of the gas phase terms (without solvation) of the Amber ff03 and ff99 potentials are examined by te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 25 publications
(55 reference statements)
3
20
0
Order By: Relevance
“…Results 3.1. Molecular structure I: torsion angles and twisting Molecular structures of both the β-stranded and helical structures of Ala 10 ( Figure 1) are very similar to those calculated previously [1], [16], [17], [18], [19] and [28]. The backbone folds of helices in membrane proteins [φ −60°, ψ −45° [29] and [30] and in water soluble globular proteins [φ −65°, ψ −40° [31] and [32] are close to each other, and are somewhat different from those of 3 10 -helices [φ −68°, ψ −18° [31] and [33].…”
Section: Methods and Computational Detailssupporting
confidence: 79%
See 1 more Smart Citation
“…Results 3.1. Molecular structure I: torsion angles and twisting Molecular structures of both the β-stranded and helical structures of Ala 10 ( Figure 1) are very similar to those calculated previously [1], [16], [17], [18], [19] and [28]. The backbone folds of helices in membrane proteins [φ −60°, ψ −45° [29] and [30] and in water soluble globular proteins [φ −65°, ψ −40° [31] and [32] are close to each other, and are somewhat different from those of 3 10 -helices [φ −68°, ψ −18° [31] and [33].…”
Section: Methods and Computational Detailssupporting
confidence: 79%
“…Consequently the 3 10 -helix must exhibit the intrinsic properties of the right-handed helical structure, since it is the most stable form when environmental effects are excluded. Several QM computations have been published on 3 10 -helical structures [16], [17], [18] and [19]. However, these studies reported electronic energies rather than thermodynamic functions.…”
mentioning
confidence: 99%
“…The error ͑intramolecular BSSE͒ produced by such superposition was found to exceed 4 kcal mol −1 when a medium-sized basis set was used. [35][36][37][38]45,46 This means that this error has the same order of magnitude as the relative energy differences of secondary structure elements of biopolymers reported in recent literature ͓see Fig. 4 and Table I ͑Ref.…”
supporting
confidence: 67%
“…12 ͒ and computational ͑molecular dynamics and quantum chemistry͒ techniques. 3,12,13,38 Their integration is expected to be particularly fruitful. 3,12,13,38 Note that in many cases, modern force fields ͓͑FF͒, e.g., Amber FF03 and FF99͒ fail to recognize the protein native structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation